Measurement of Plasma Potential using Deceleration technique. (July 2015) - Sairam, T; Bhatt, Pragya; Kumart, Ajit; Kumar, Herendra; Rajput, J; Safvan, C P
Synopsis: We report a novel technique to measure the plasma potential. In this technique, we extract an ion beam into the chamber with few keV of energy and then decelerate it using series of electrodes till the deceleration potential nullifies the extraction potential and measure the retaining energy of the beam using retarding plate analyzer (RPA) to determine the plasma potential.